Outcomes of Early Development of Hyponatremia in Acute ST-Elevated Myocardial Infarction Patients: A Study in a Tertiary Hospital - Sowdagar, Mohammad Nizamul Hossain; Ahmad, Mushtaq; Khan, AKM Musa; Jabbar, Zahida; Rahman, Md Mukhlesur; Sultan, Md Ashraf Uddin (University Heart Journal, 2020)
Background: Coronary heart disease is a global health problem and a major cause of death in both developed and developing countries. Clinical importance of hyponatremia in ST-elevated acute myocardial infarction (STEMI) is an important topic of study among present researchers. Objective: To assess the outcomes and prognostic implications of early development of hyponatremia inhospitalized acute ST-elevated myocardial infarction patients. Methods: This is a prospective observational study performed in the department of Cardiology, Combined Military Hospital (CMH), Dhaka from July 2018 to June 2019. A purposive sampling technique was used on 82 patients with ST-elevated acute myocardial infarction admitted in CCU and treated with thrombolysis. They were evaluated for serum sodium level at admission and at 48 hours after admission. Here sodium concentration <135 mmol/L is defined as Hyponartemia. Fourty one patients with hyponatremia were included in Group-I and 41 patients with normal sodium level were included in Group-II. Then the in-hospital outcome variables were analyzed. Results: Among the study population 86.58% were male and 13.42% were female. Age range was 25 years to 74 years. Considering risk factors highest percentage of study population in group- I had hypertension (60.97%) followed by dyslipidemia (51.21%), diabetes mellitus (51.21%), history of smoking (53.60%), and family history of Coronary Artery Disease (CAD) (31.14%). There were five outcome variables such as heart failure, cardiogenic shock, arrhythmia, duration of hospital stay and death. 10 patients died in Group-I and 2 patients died in Group-II. Among the outcome variables death, heart failure and hospital stay was more in Group-I and was statistically significant. hospital outcome of study population according to serum sodium level. Considering in hospital outcome heart failure occurred in 14 patients (p= .001), arrhythmia developed in 17 patients (p=0.108), cardiogenic shock occurred in 9 patients (p=0.354) and death occurred in 10 patients (p=0.002). P-Value of heart failure and death was statistically significant. Conclusion: Early developed hyponatremia in patients with ST-elevated acute myocardial infarction was an independent predictor of prognosis. It has been found that heart failure, duration of hospital stay and death was more in hyponatremic patients and prognosis worsen with increasing severity of hyponatremia. Plasma sodium level may serve as a simple marker to identify patients at high risk. University Heart Journal Vol. 17, No. 1, Jan 2021; 16-21